2010
DOI: 10.1111/j.1708-8305.2010.00424.x
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review and Meta‐Analysis of TST Conversion Risk in Deployed Military and Long‐Term Civilian Travelers

Abstract: The overall cumulative incidence of 2.0% is what could be expected to occur among the local population in many developing-country settings, though TST conversion likely overestimates the risk of TB infection because of the low positive predictive value (PPV) of the TST in low-prevalence populations such as travelers. To maximize the PPV of a screening test for LTBI, a targeted testing strategy for long-term military and civilian travelers is recommended, based on exposures known to increase the risk of TB. Stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 29 publications
0
5
1
Order By: Relevance
“…7,8 The only prospective study among long-term travelers found an incidence of 1.8%, 7 which was three times higher than that seen in our study. These differences are largely attributable to the heterogeneity between and within these populations.…”
Section: Discussioncontrasting
confidence: 53%
See 2 more Smart Citations
“…7,8 The only prospective study among long-term travelers found an incidence of 1.8%, 7 which was three times higher than that seen in our study. These differences are largely attributable to the heterogeneity between and within these populations.…”
Section: Discussioncontrasting
confidence: 53%
“…Duration of deployment is variable among both units and individuals, so incidence rates may be a better reflection of TB transmission, although this has not been the case in previous studies. 8 On the other hand, the TST is known to have poor positive predictive value in low-risk populations like the U.S. Army, 9 so many of the incident cases in both groups may have been false positives, resulting in non-differential misclassification and overestimates of incidence. Since two-step testing is not performed in basic training, subsequent testing may also have resulted in boosted reactions, which could overestimate the true incidence of infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[25][26][27] It also compares favorably with the 2% (99% CI 1.6-2.4) incidence for travelers calculated in a recent meta-analysis. 28 Compared with another group of aid workers, a study of TB conversions in Peace Corps volunteers 26 reported very similar prevalence and conversion rates (2.3% converting at a rate of 1.3/1,000 pm). Compared with NZ Police (who deploy to similar destinations but for shorter periods of time), VSA volunteers appeared to have both higher conversion prevalence and conversion rates (although these were not statistically significant).…”
Section: Figure 1 Reported Percentage Of Dengue Fever Virus (Dfv) Conmentioning
confidence: 73%
“…TB has a specific importance among respiratory infections because it can spread through respiratory contact and requires strict isolation conditions in hospitals, and because there is an important threat of resistant cases (Matteelli et al 2005). Although the prevalence of TB has greatly decreased in the temperate and developed counties of Western Europe, North America, Australia, and Japan, it remains a major disease burden in tropical and developing countries (Freeman et al 2010;Corbett et al 2003). Consequently, travelers and expatriates from low-prevalence nations who travel to or live in high prevalence nations may become infected with TB (Cobelens et al 2000).…”
Section: Epidemiology Of Respiratory Tract Infections Among Travelersmentioning
confidence: 99%